Review on Digital Twin in Pharmaceutical and Biopharmaceutical Manufacturing - Kamini Ghavat,; Swati Wakchoure,; Pooja Surve,; Nishita Hole, (International Journal of Scientific Research in Science and Technology, 2024)
The rise of Industry 4.0 technologies fosters the creation and use of digital twins (DT), which aids in transforming the manufacturing sector into a more responsive and intelligent domain. DTs are digital replicas of physical systems that emulate the behavior and dynamics of those systems. A comprehensive DT integrates physical elements, virtual components, and the data exchange between them. Integrated DTs are being utilized across various processes and product sectors. Although the pharmaceutical industry has recently progressed by adopting Quality-by-Design (QbD) initiatives and is in the midst of a digital transformation to integrate Industry 4.0, there has yet to be a complete DT implementation in pharmaceutical manufacturing. Consequently, it is essential to evaluate the advancements of the pharmaceutical sector in adopting DT solutions. This narrative literature review aims to provide an overview of the current state of DT development and its application in pharmaceutical and biopharmaceutical production. Additionally, it addresses the challenges and opportunities for future research in this area.
Keywords: digital twin; Industry 4.0; pharmaceutical manufacturing; biopharmaceutical manufacturing; process modeling